THE ROOTS OF THE PEDAGOGICAL VIEWS AND SPIRITUAL AND MORAL IDEAS OF THE KHOREZM JADIDS - Ibodullayeva Zubayda Sherzodovna; Ibodullayev Islombek (Recent scientific discoveries and methodological research, 2025)
In examining the roots of the pedagogical views and spiritual and moral ideas of the Khorezm Jadids, it is essential to contextualize their educational ideology within the broader spectrum of Central Asian societal transformations during the late 19th and early 20th centuries.